PENANGANAN GANGGUAN PADA PERANGKAT METRO-ETHERNET DI PT.TELEKOMUNIKASI INDONESIA,Tbk AREA NETWORK SOLO , JAWA TENGAH - , NUR FEBRIYANTO, Nur Sulistyawati, S.T, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ethernet is a technology originally used for data communications on a computer network within a limited area, generally at a company (LAN) but, due to high customer demand in the delivery of data and voice so that the telecommunications company that is PT.Telekomunikasi Indonesia, Tbk using a device not only to a limited area coverage. So, need something a tool to support the growing use of systems in the telecommunications world that is Metro Ethernet. Metro Ethernet device uses a fiber-optic cables are the type of Fast Ethernet and Giga Erhernet with speeds up to 1000 Mbit / second so that the transmission to the customer very cepat.Selain, the Metro Ethernet device has a data capacity to store up to 320GB. However, PT.Telekomunikasi Indonesia, Tbk only use two types of Metro Ethernet devices are Tellabs 8830 and Tellabs 8840. The amount of capacity to tellabs 8830 amounted to 80GB and 160GB tellabs 8840 registration and use of each of these devices depends on the needs of customers in a region.